Amigo. (2010). Written and directed by John Sayles. Starring Chris Cooper, Garret Dillahunt, DJ Qualls, Lucas Neff, Yul Vazquez, Joel Torre, Bembol Roco, Pen Medina, Irma Adlawan, Rio Locsin. Produced by Maggie Renzi. United States. - Reilly, Brandon (Social Science Diliman: A Philippine Journal of Society and Change, 2011)
None
Keywords: None